A potential high risk for fatty liver disease was found in mice generated after assisted reproductive techniques. Issue 2 (12th September 2017) - Gu, Leilei; Zhang, Jingjing; Zheng, Meimei; Dong, Guoying; Xu, Jingyi; Zhang, Wuyue; Wu, Yibo; Yang, Yang; Zhu, Hui
Abstract: Abnormal gametogenesis and embryonic development may lead to poor health status of the offspring. The operations involved in the assisted reproductive technologies (ARTs) occur during the key stage of gametogenesis and early embryonic development. To assess the potential risk of abnormal lipid metabolism in the liver of adult ARTs offspring, two ARTs mice models derived from preimplantation genetic diagnosis (PGD group) and in vitro cultured embryos without biopsy (IVEM group) were constructed. And control mice were from in vivo naturally conceived (Normal group). The results showed that ARTs offspring had increased body weight and body fat content comparing to normal group. An increasing volume and amount of lipid droplets as well as lipid droplet fusion were found in the hepatocytes of ARTs mice, and a significantly increased liver TG content was also shown in the ARTs mice, which due to the increased TG synthesis and decreased TG transport in the liver. All the results indicated that the manipulations involved in ARTs might play an important role in the lipid accumulation of adult offspring. By analyzing the DNA methylation profiles of 7.5dpc embryos, we proposed that methylation deregulation of the genes related to liver development in ARTs embryos might contribute to the abnormal phenotype in the offspring. The study demonstrated that ARTs procedures have adverse effect on liver development which resulted in abnormal lipid metabolism and induced the potential high risk of fatty liver in adulthood. Abstract : Our study indicated that the ARTs procedure could be the potential embryo‐fetal reason for fatty liver disease and the procedure might influence the embryos DNA methylation resulting in abnormal liver development and function.